2017
DOI: 10.1088/1361-6463/aa87ab
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear electric field effect on perpendicular magnetic anisotropy in Fe/MgO interfaces

Abstract: The electric field effect on magnetic anisotropy was studied in an ultrathin Fe(001) monocrystalline layer sandwiched between Cr buffer and MgO tunnel barrier layers, mainly through post-annealing temperature and measurement temperature dependences. A large coefficient of the electric field effect of more than 200 fJ/Vm was observed in the negative range of electric field, as well as an areal energy density of perpendicular magnetic anisotropy (PMA) of around 600 J/m 2 . More interestingly, nonlinear behavior… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…In addition to ultrathin epitaxial films with large PMA [35,59,60,61,62,63,64,65,66,67], VCMA effects have been observed in various materials systems, for example, in sputter-deposited CoFeB [68,69,70,71,72,73,74,75,76,77,78,79,80,81], which is an important practical material that is used in the mass production of MTJs, and in self-assembled nano-islands [82], nanocomposite structures [83], and ultrathin layers with quantum well states [84]. The VCMA effect can also be applied for the control of domain wall motion [85,86,87] and magnetic skyrmions [88,89,90].…”
Section: Overview Of the Vcma Effect And Voltage-induced Dynamic Smentioning
confidence: 99%
“…In addition to ultrathin epitaxial films with large PMA [35,59,60,61,62,63,64,65,66,67], VCMA effects have been observed in various materials systems, for example, in sputter-deposited CoFeB [68,69,70,71,72,73,74,75,76,77,78,79,80,81], which is an important practical material that is used in the mass production of MTJs, and in self-assembled nano-islands [82], nanocomposite structures [83], and ultrathin layers with quantum well states [84]. The VCMA effect can also be applied for the control of domain wall motion [85,86,87] and magnetic skyrmions [88,89,90].…”
Section: Overview Of the Vcma Effect And Voltage-induced Dynamic Smentioning
confidence: 99%
“…These correspond to +0.44 and −2.16 erg/cm 2 (≡ mJ/m 2 ). The electrons depletion increased the out-of-plane MAE, same as the interfaces of Fe/MgO[37][38][39][40][41][42][43] and (Fe,Co)/Pt/MgO…”
mentioning
confidence: 85%
“…For example, Noguchi et al reported VC-MRAM circuits for ultralarge last level cache memory, in which the voltage to switch the magnetization is as high as 2.2 V [10], which is larger than the standard CMOS power-supply voltage of less than 1.2 V. The necessity of such a large voltage originates from limited amounts of anisotropy modulation coefficients by E-field. To overcome this issue, the material development of the free-layer material is now underway [88][89][90][91][92]. Another issue to be addressed is the small time window for the writing.…”
Section: Progress Of Vc-mrammentioning
confidence: 99%